(untitled) - J M Hunter [et al.] (Geneva, 1993)
The book reviews the effects of water resources development on four parasitic diseases - schistosomiasis, malaria, lymphatic filariasis, and onchocerciasis - stressing that, with current knowledge, these diseases are amenable to prevention or control. It discusses the actions that could have mitigated the adverse effects. Throughout the analysis, the book also stresses the need for the health sector to be actively involved in intergrated development activities, incorparating health protection and promotion measures along economic advancement
Keywords: diseases vectors,health policy,parasitic diseases - prevention and control,water resources development